DYNAMICS OF DECOMPOSITION AND LIBERATION OF NUTRIENTS OF BLACK OAT AND TURNIP FOODER STRAW CUT IN DIFFERENT STAGE OF DEVELOPMENT - LANG, Claudete Reisdörfer (Scientia Agraria, 2002)
The dynamics of nutrient (N, P, K, Ca and Mg) decomposition and release from winter litter mulching of black oat (Avena strigosa Schreb) and turnip (Raphanus sativus L.) were studied during a 8,5 month period. Factorial randomized blocks were used as the experimental design. A combination of the two mentioned soil mulchings cut at three development stages was used. These were: vegetative (94 days), flowering (103 days) and full flowering (116 days). Harvested material was put into small nylon bags that were scattered on the soil and recovered after five periods of four weeks each for content examination. Results were submitted to variance and regression analysis. Adjustment to a mathematical model indicating mass loss was made according to BADRE et alii, (1998). The experimental model relates the mass decomposition rate as well as nutrient release as a quadratic function on time (t). the mathematical model used was: M(t) = M(o). Exp. T (a t + b). The dry mass production presented no differences between species. It was higher under flowering and full flowering conditions when compared to the vegetative phase for oat as well as for turnip (p < 0,01). The exponential model was adjusted to the obtained dry mass (DM) mineralization rate according to its harvest time (p < 0,01) for both species and their respective development phases. Coefficients found varied according to differences observed on carbon/phosphor (C/P) ratio and cellulose and hemicelulose (NDF) content of the species (p < 0,01) and not between the above mentioned development phases (p > 0,05). The carbon/nitrogen (C/N) ratio and lignin, silica and cutin (ADF) were both different between the different phases (p < 0,05), but not between species (p > 0,05). In terms of nutrient release the exponential model used was highly significant (p < 0,01) for all nutrients independently of the species studied and their development phases.